Dermatological assessment of thick-skinned patients before rhinoplasty: What may surgeons ask for? : Review - Saadoun, Rakan; Risse, Eva-Maria; Crisan, Diana; Veit, Johannes Adrian (International journal of dermatology, 2023)
Rhinoplasty is considered a very challenging surgery since minimal changes of this central area of the face may significantly impact a person's appearance and self-awareness. This is even more challenging in thick-skinned patients because results are less predictable, and changes to the osseocartilaginous framework (OCF) may not be sufficiently visible due to the blanket effect of the thick skin. Furthermore, pre-existing skin conditions may exacerbate following surgery. Therefore, managing patients with extremely thick skin or patients who suffer from pre-existing dermatological conditions such as rosacea or acne requires a synergy of surgeons and dermatologists to achieve optimal results. In this article, we review the most significant pre- and post-surgical regimens that surgeons and dermatologists should apply in selected patients to achieve optimal results after rhinoplasty.
Erstmals veröffentlicht: 03. Juli 2022
Gesehen am 23.07.2024